2015
DOI: 10.3346/jkms.2015.30.5.586
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Fibroblast Growth Factor 21 and Coronary Artery Disease in Patients with Type 2 Diabetes

Abstract: The aim of this study was to evaluate the association of plasma fibroblast growth factor (FGF)-21 with angiographically significant coronary artery disease (CAD) in patients with type 2 diabetes mellitus. Serum FGF-21 was measured in 120 patients undergoing coronary angiography. Patients were divided into 4 groups based on the presence/absence of type 2 diabetes mellitus and of significant CAD. The atherosclerotic burden was obtained by two angiographic scores: Gensini score (GS) and Extent score (ES). FGF-21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 18 publications
3
27
0
Order By: Relevance
“…In a study involving 100 Chinese subjects, with 38% of them having T2DM, serum FGF21 levels were independently associated with the presence of acute myocardial infarction and were significantly higher in those who developed reinfarction within 30 days 15. However, conflicting results were also reported from a few studies, which showed a lack of significant association after adjusting for body mass index and glycemic status 16, 17. Given that circulating FGF21 levels were higher in T2DM,6, 9 and most cross‐sectional studies consisted of relatively small sample size and therefore a limited number of subjects with T2DM, the association of serum FGF21 with CHD in T2DM could only be, at most, speculative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study involving 100 Chinese subjects, with 38% of them having T2DM, serum FGF21 levels were independently associated with the presence of acute myocardial infarction and were significantly higher in those who developed reinfarction within 30 days 15. However, conflicting results were also reported from a few studies, which showed a lack of significant association after adjusting for body mass index and glycemic status 16, 17. Given that circulating FGF21 levels were higher in T2DM,6, 9 and most cross‐sectional studies consisted of relatively small sample size and therefore a limited number of subjects with T2DM, the association of serum FGF21 with CHD in T2DM could only be, at most, speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, the association of circulating FGF21 with CHD in T2DM has not been clearly defined. In cross‐sectional studies, conflicting results were reported regarding circulating FGF21 levels in subjects with CHD, with an association of raised FGF21 levels with CHD reported in some studies,13, 14, 15 but not in others 16, 17. The association of circulating FGF21 with CHD in T2DM, especially among those without known cardiovascular disease (CVD), remains to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al 10 showed that serum FGF21 levels measured in 120 patients are significantly However, the number of patients involved in studies of the correlation between serum FGF21 and coronary artery severity is so far quite small, and further investigations will be required to clarify whether such a correlation exists, and if it does, to determine its precise nature.…”
Section: Discussionmentioning
confidence: 99%
“…2 Moreover, serum FGF21 concentrations are associated with established cardiovascular risk factors, and are higher in patients with CAD than in those without CAD. 5,10 However, the precise nature of the association between serum FGF21 concentrations and CAD has yet to be confirmed. 4,11,12 In this study, we compared serum FGF21 concentrations in individuals with or without coronary artery narrowing, as identified by coronary angiography (CAG), and determined whether circulating FGF21 concentrations are associated with the severity of CAD.…”
Section: Introductionmentioning
confidence: 99%
“…We report here, for the first time, that 280M genetic variants of CX3CR1 are also significantly associated with decreased risk for CAD in patients with T2DM. Diabetes mellitus and vascular inflammation leading to CAD is a multifactorial process involving various chemokines (20), scavenger receptors (20), monocytes, endothelial cells, vascular smooth muscle cells (22,23) and growth factors (24,25), which function in disarray, leading to the diabetic vascular disease phenotype. Polymorphisms in CX3CR1 result in reduced chemokine binding.…”
Section: Discussionmentioning
confidence: 99%